POTENCIAL DE CONTROLE DE TOMBAMENTO DE PLÂNTULAS CAUSADAS POR FUNGOS DE SOLO COM PRODUTOS BIOLÓGICOS NAS CULTURAS DA SOJA E DO FEIJÃO - Les, Nathaly (2016)
Among the diseases found in soybeans and beans, those of particular note are fungi found in the soil, of which the most important are Fusarium solani and Rhizoctonia solani. Controlling these diseases is difficult; the use of fungicides applied to the aerial parts is ineffective and treating seeds with fungicides is the most widely used method. However, in order to reduce the environmental impact alternative disease control measures have been sought such as the use of biological products. Consequently, the objective of this study was to evaluate the effectiveness of different biological products in the control of soil fungi (F. solani and R. solani) in relation to plant vigor, germination and growth promotion in bean and soybean crops. The experiments were conducted in duplicate in the Applied Plant Pathology Group laboratories and in the greenhouse of the State University of Ponta Grossa (UEPG) in 2015. The experimental design was entirely randomized blocks with 10 treatments and 4 replicates. The treatments were as follows: 1 - control without inoculation;control with inoculation; 3 - Trichoderma asperellum (Quality); 4 - Trichoderma harzianum (Trichodermil); 5 - Trichoderma harzianum (Ecotrich); 6 - Coniothyrium minitans (Coniothyrium); 7 - Bacillus subtilis (Serenade); 8 - Bacillus pumilus (Sonata); 9 – thiophanate-methyl + fluazinam (Certeza); 10 - fludioxonil + metalaxyl-M (Maxim XL). The blotter test and tests of plant vigor and germination were performed in the laboratory. The following were evaluated in the greenhouse:the initial and final emergence of seedlings; pre and post-emergence damping-off; the lengths of roots and aerial parts; fresh and dry weight; and the incidence and severity of both fungi. It was concluded that the best treatment for all the evaluated parameters was fludioxonil + metalaxyl-M. Apart from this treatment, for some parameters as root length and shoot and reduction in the incidence and severity of diseases the treatments with thiophanate-methyl + fluazinam, and the biological products based on Bacillus were also found to be efficient. The treatments based on T. harzianum and C. minitans were inefficient in the tested conditions.